2018
DOI: 10.1111/jocn.14258
|View full text |Cite
|
Sign up to set email alerts
|

Patient agitation and its management in adult critical care: A integrative review and narrative synthesis

Abstract: The importance of ensuring patients are re-orientated regularly and signs of agitation assessed and acted upon promptly is reiterated. Early identification of specific patient profiles such as those with previous high alcohol or psychoactive drug habit may enable more proactive management in agitation management rather than reactive. The prompt liberation from the restriction of ventilation and encouragement of family or loved ones involvement in care need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…This review adds knowledge regarding the identified rationales and determinants for restraint use in clinical practice and suggests that guidance is not consistently followed. Previous studies have highlighted uncertainties regarding the efficacy of physical restraint in preserving patient safety (Freeman, Yorke, & Dark, ) and the impact of nurses' beliefs on restraint use (Via‐Clavero et al, ). This review builds on these studies by exploring how the decision to apply restraint is made through an identification of patient, nurse and environment‐centred determinants and influences.…”
Section: Discussionmentioning
confidence: 99%
“…This review adds knowledge regarding the identified rationales and determinants for restraint use in clinical practice and suggests that guidance is not consistently followed. Previous studies have highlighted uncertainties regarding the efficacy of physical restraint in preserving patient safety (Freeman, Yorke, & Dark, ) and the impact of nurses' beliefs on restraint use (Via‐Clavero et al, ). This review builds on these studies by exploring how the decision to apply restraint is made through an identification of patient, nurse and environment‐centred determinants and influences.…”
Section: Discussionmentioning
confidence: 99%
“…Critically ill patients admitted to intensive care units (ICU) often need more invasive operations (e.g., mechanical ventilation and hemodialysis) due to the needs from their condition (4), which can also lead to acute pain, discomfort, sleep deprivation, agitation, and delirium (5). Agitation, for example, can propel patients to resist the ventilator, thus increasing the oxygen consumption, causing them to accidentally remove various devices and catheters on them and even posing life-threatening risks (6). Therefore, the main reason for the use of PR around ICU is to prevent patients from accidentally removing the catheters or devices needed to protect their safety (7).…”
Section: Introductionmentioning
confidence: 99%
“…The definition of PR is "Any action or procedure that prevents a person's free body movement to a position of choice and/or normal access to his/her body by the use of any method, attached or adjacent to a person's body that he/she cannot control or remove easily" (8). Although PR was used to prevent UE, there were many studies that proved PR is one of the risk factors that account for UE and cannot protect patient safety (6,9). Indeed, its use has been proven to cause pressure injuries (10) and worsen agitation (11), delirium (12), and neurovascular complications (13).…”
Section: Introductionmentioning
confidence: 99%
“…These stressors can agitate the patients and increase their anxiety [3,4]. Evidence shows that agitated patients are at increased risk of self-extubation, requiring re-intubation [5,6]. In addition, agitation and anxiety increase patients' needs for opioids and benzodiazepines [5], the interventions that can have significant adverse effects, such as respiratory depression, hypotension, urinary retention, and nausea and vomiting [7].…”
Section: Introductionmentioning
confidence: 99%